PELATIHAN PENGEMBANGAN HUBUNGAN KELOMPOK KERJA DENGAN INDUSTRIAL DALAM MENINGKATKAN KUALITAS USAHA DAN KESEJAHTERAAN KELOMPOK KERJA - Karta Negara Salam, karta; Daga, Rosnaini; Hamzah, Nasir; Suwandaru, Rachman; Ashary, Muhammad; Pasae, Panus; Rinaldi, Rinaldi (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of implementing this training is to provide understanding to the training participants regarding the Development of Working Group Relations with Industrial in Improving Business Quality and Working Group Welfare, those attending the training are business owners who employ several people as employees. These business owners are given education so they are able to establish good relations with employees. Training participants can create Industrial Relations and Labor Welfare, are able to plan, coordinate, implement and control activities in the field of Industrial Relations and Labor Welfare because in an organization or company, there is not only a relationship based on professionalism between the company and its employees, but an organization A successful company must have good industrial relations or industrial relations between management and workers